Use of Gabapentin, Esmolol or Their Combination to Attenuate Haemodynamic Response to Laryngoscopy and Intubation - Shrestha, G S; Marhatta, M N; Amatya, R (Kathmandu University Medical Journal, 2012)
Background Laryngoscopy and intubation increases blood pressure and heart rate. Objective The study aims to investigate the effect and safety of gabapentin, esmolol or their combination on the haemodynamic response to laryngoscopy and intubation. Methods A total of 72 patients undergoing elective surgery were randomly allocated to one of the four groups. First study drug was administered orally as gabapentin 1200mg or placebo. Second study drug was administered intravenously as esmolol 1.5mg/kg or normal saline. Heart rate, rate pressure product, systolic blood pressure and mean arterial pressure were recorded at baseline and at zero, one, three and five minutes after tracheal intubation. Results Baseline values were compared with the values at various time intervals within the same group. In group PE (placebo, esmolol), there was significant decrease in heart rate and rate pressure product at five minutes. In group GN (gabapentin, normal saline), there was significant decrease in systolic blood pressure and mean arterial pressure at five minutes. In group GE (gabapentin, esmolol), there was significant decrease in heart rate at zero, three and five minutes. Systolic blood pressure, mean arterial pressure and rate pressure product was significantly lower at three and five minutes. In group PN (placebo, normal saline), there was significant increase in heart rate at zero, one, three and five minutes; systolic blood pressure at zero and one minutes; mean arterial pressure at zero and one minutes & rate pressure product at zero, one and three minutes. In group GN (gabapentin, normal saline), there was significant increase in heart rate at zero, one and three minutes & rate pressure product at zero, one and three minutes. In group PE (placebo, esmolol), there was significant increase in systolic blood pressure at zero and one minutes & mean arterial pressure at zero and one minutes. However, in group GE (gabapentin, esmolol) none of the variables showed statistically significant increase at any time. Inter-group comparison was made for each time point. At zero minute, there was significant difference in heart rate between groups PN and GE, GN and PE & GN and GE Significant difference was also noted in rate pressure product between PN and GE at zero minute. At one minute there was difference in heart rate between PN and PE, PN and GE, GN and PE & between GN and GE. Significant difference was observed in rate pressure product between PN and PE & between PN and GE at one minute. No significant side effects of the study drugs were observed. Conclusions Combination of gabapentin and esmolol in this study design is safe and better attenuates both the pressor and tachycardic response to laryngoscopy and intubation, than either agent alone. DOI: http://dx.doi.org/10.3126/kumj.v9i4.6336 Kathmandu Univ Med J 2011;9(4):238-43